Aeronautical imagination and the figure of the French aviator in the Azorean press (1935/1949) - Faria, Dominique (2020)
Submitted by Dominique Faria (dominiquefaria@uac.pt) on 2020-01-23T15:52:52Z No. of bitstreams: 1 Aeronautical imagination and the figure of the French aviator in the Azorean press (1935_1949).pdf: 2449584 bytes, checksum: 3ae2bb4e2dd365c6c19fd153262cfe1d (MD5)